Bayzze Apps: Pembangunan Aplikasi Pemesanan Camilan serta Minuman pada Bayzze Store Berbasis Android - Ambya, Denna Auliya Putri; Cahyana (eProceedings of Applied Science, 2024)
Small and Medium Enterprises (MSMEs) have important role in Indonesia's economic growth. MSMEs are the mainstay of the economic sector and provide the greatest employment opportunities. Number of MSMEs in Indonesia reached 64.19 million with a contribution of 61.97% to gross domestic product (GDP). MSMEs are capable absorbs 97% of the workforce and attracts up to 60.4% of the total investment. In the era of digital revolution 4.0, information technology and Communication has a big influence. Bayzze Store, one of the MSME providers in Bandung, West Java, still using a less efficient manual ordering system. Therefore, the Bayzze Apps application was developed for supports the process of ordering snacks and drinks. This application not only provides information and the latest product recommendations, but also provides features support such as product details, order history, and product search. This application allows prospective buyers make orders easily and effectively, increase purchase intentions and provide economic benefits for sellers and local communities. Extreme programming used as a development and implementation method done using Android Studio and language Kotlin programming. Firebase API is used to store and coordinate data in your applications. This research using BlackBox Testing as a testing technique the system. The Bayzze Apps application is expected to create MSMEs don't just improve performance and adapt with technological developments, but also contribute positive for the local economy and empowerment public. Keyword: UMKM, Android, Kotlin, Firebase.